Case Report-Amlodipine Toxicity - Surendran, Kavya; S, Karthika; MK, Krishnapriya; Jetto, Dona Maria (Journal of Pharmacy Practice and Community Medicine)
Amlodipine is a dihydropyridine calcium channel blocker mainly indicated in the treatment of essential hypertension and angina pectoris. Overdose of calcium channel blocker, Amlodipine results in toxicity along with profound hypotension and shock. Here, a 20-year-old female patient was admitted to the MICU with complaints of severe breathing difficulty, and multiple episodes of vomiting one day earlier. After the chest x-ray, ECG, and blood investigations, she was diagnosed as having Amlodipine toxicity, pulmonary edema, circulatory shock, hypocalcemia, hypokalemia, systemic hypotension, and acute kidney injury. She was discharged from the hospital after the symptoms had recovered.
Keywords: Calcium channel blockers; Amlodipine; Drug overdose; Dihydropyridine; Hypotension; Toxicity